Effect of Phosphorylation Sites Mutations on the Subcellular Localization and Activity of AGPase Bt2 Subunit: Implications for Improved Starch Biosynthesis in Maize - Guowu Yu; Noman Shoaib; Yang Yang; Lun Liu; Nishbah Mughal; Yuewei Mou; Yubi Huang (Agronomy, 2023)
ADP-Glc pyrophosphorylase (AGPase) is a pivotal enzyme catalyzing the conversion of ATP and glucose-1-phosphate (Glc-1-P) to adenosine diphosphate glucose (ADP-Glc), thereby serving as a rate-limiting factor in starch biosynthesis in crops. Although previous investigations have suggested phosphorylation-based regulation of AGPase in maize, the explicit modulation mechanisms have yet to be elucidated. This research evaluated the effect of point mutations at phosphorylation sites (identified using iTRAQTM AB SCIEX, Framingham, MA, USA) on the subcellular localization and activity of the AGPase small subunit Bt2, and its interaction with the large subunit Sh2, in maize. Despite the induction of point mutations, subcellular localization of the Bt2 subunit remained unaltered, primarily within the cytoplasm and nucleus. The interaction between Bt2 and Sh2 subunits continued, mainly in the chloroplast. Notably, an increase in AGPase activity was observed in the case of simulated phosphorylation point mutations, whereas dephosphorylation activity significantly diminished relative to the wild type. These findings demonstrate that point mutations do not affect the subcellular localization of the Bt2 subunit or its interaction with the Sh2 subunit, but substantially modulate AGPase activity. This study provides critical insights into the role of point mutations in enhancing AGPase activity, thus potentially accelerating the production of ADP-Glc, the primary substrate for starch synthesis, promising implications for improved starch biosynthesis in maize.